Odpowiedzi

Najlepsza Odpowiedź!
2010-02-21T15:48:31+01:00
A)
(-6)x[2-(-3)+3x(-1)]=
(-6)*[2+3+(-3)]=
(-6)*2 =-12

b)
-12+12x[-(-6):3-3]=
0*[6:3-3]=
0*(-1) = 0

c)
0,75x(-4/5)-2 1/2 x (-0,24)=
0,75*(-0,8)-2,5*(-0,24)=
-0,6+0,6 = 0

d)
[ 2/5 - (-0,4) : (-0,12)] : [4-(-44)]=
[0,4-1/3]:48=
1/15:48 = 1/720

e)
4/5 - (1,2 x 5/12 - 0,8 ) : (-1/8) =
0,8-(1/2-0,8):(-0,125)=
0,8+0,3:(-0,125) =
0,8-2,4 = -1,6
1 4 1
2010-02-21T16:02:09+01:00
A) (-6)*[2-(-3)+3*(-1)] = (-6)*[5-3] = (-6)*2 = -12
b) -12+12*[-(-6):3-3] = -12+12[6*3-3] = -12+12*(-1) = -12-12 = -24
c)0,75*(-4/5)-2,5*(-0,24) = -0,6+0,6 = 0
d) [2/5-(-0,4):(-0,12)]:[4-(-44)] = [0,4 - 10/3]:48 = [4/10 - 10/3]:48 = [12/30-100/30]:48 = [-88/30]:48 = [-88/30]*1/48 = -88/1440 = -22/360 = -11/180
e) 4/5- (1,2*5/12-0,8):(-1/8) = 4/5-(0,5-0,8):(-1/8) = 4/5-(-0,3):(-1/8) = 4/5-2,4 = -1,6
2 5 2